Can the Generalist Predator Calosoma chinense Kirby Be Effectively Employed in the Biological Control of Spodoptera frugiperda (J. E. Smith)? - Caihong Tian; Jianrong Huang; Junyi Zhang; Guoping Li; Xuezheng Hao; Lin Wang; Xinming Yin; Hongqiang Feng (Insects)
Calosoma chinense Kirby, a generalist predator, consumes a variety of pests. To better understand its predatory behavior and capacity, particularly against Spodoptera frugiperda (J. E. Smith), we identified the field species and investigated the predation capacity of the third-instar larvae and adults of both sexes against the first- to sixth-instar larvae, pupae, and male and female adults of S. frugiperda. The predation preference for different developmental stages of S. frugiperda was further examined. Our results indicated that C. chinense can prey on S. frugiperda in various stages, including larvae and adults, demonstrating robust predatory abilities. Among them, female adults of C. chinense exhibited the strongest predatory ability against first-instar larvae of S. frugiperda, with the highest daily consumption of 38.90 ± 0.79 individuals. The first-instar larvae of C. chinense also showed a certain predatory ability towards S. frugiperda, with a daily consumption of 6.95 ± 0.88 individuals per predator. The predation ability of C. chinense larvae increased with larval growth, especially for the first to third instar of S. frugiperda larvae, and C. chinense female adults had the strongest predation ability, followed by male adults and then third-instar larvae. However, there was no significant difference in predation capacity against fourth- to sixth-instar larvae and male and female adults of S. frugiperda, nor between adults of both sexes and third-instar larvae of C. chinense. The predation choice experiment revealed that the third-instar larvae and male and female adults of C. chinense showed a positive preference for S. frugiperda larvae from the first to fourth instars, while for the fifth- to sixth-instar larvae, they exhibited a negative preference. Overall, C. chinense exhibited a strong ability to prey on S. frugiperda. Our study indicates that C. chinense has the potential for application in the biological control of S. frugiperda.